STUDENT LITERACY TRANSFORMATION IN THE DIGITAL AGE: THE EFFECT OF DISCOVERY BASED READING WITH LEVELED BOOKS ON CRITICAL READING COMPREHENSION - Nandia Kiranti; Yeni Yuniarti; Dinie Anggraeni Dewi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research was conducted to address various problems of low levels of critical reading comprehension skills of students. Reading comprehension is a reading activity that aims to obtain information contained in the reading text. This research is motivated by the low level of reading ability, especially in reading comprehension. This study aims to determine the effect of the discovery-based reading method on the critical reading comprehension skills of elementary school students. The method used is a quasi-experimental design with the Matching-Only Pre-test-Post-test Control Group Design, involving fifth-grade students in two schools in Bandung Regency. The average pre-test of the experimental class is 52.0833 and the post-test of the experimental class is 88.7500 so that in the experimental class there is an increase. The average pre-test value of the control class is 37.4000 and the post-test of the control class is 76.9000 so that in the control class there is an increase. The highest score in the post-test of the experimental class was 100 and the lowest score in the post-test of the experimental class was 80. The highest score in the post-test of the control class was 82.5 and the lowest score in the post-test of the control class was 65. There was no difference in the influence of critical reading comprehension ability between those using the discovery-based reading method and those using the SQ3R method.